Occurrence of Anastrepha fraterculus and Ceratitis capitata (Diptera: Tephritidae) in Organically Grown Rubus (Rosales: Rosaceae), in Two Contrasting Environments of Northwestern Argentina - Funes, Claudia Fernanda; Escobar, Lorena Ines; Meneguzzi, Natalia Gabriela; Ovruski Alderete, Sergio Marcelo; Kirschbaum, Daniel Santiago (2018)
In Tucumán (northwestern Argentina) during 2013 and 2014, Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae) and Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) were found infesting organically grown blackberries in the humid piedmont region (Monte Grande, Famaillá). In 2016, only A. fraterculus was found infesting organically grown blackberries and raspberries in the temperate semiarid region (Tafí del Valle), where studies conducted in prior years showed coexistence of both fruit fly species with prevalence of C. capitata over A. fraterculus, but in other fruit species. In this study, we found that A. fraterculus had a remarkable preference for raspberries over blackberries. These are the first records of fruit fly occurrence in Rubus (Rosales: Rosaceae) in northwestern Argentina and expand the range of host species for fruit flies in the region. Fruit fly infestation levels in blackberries in the humid region were very low, whereas fruit fly infestation in the semiarid region was relatively high. Based on our observations, we hypothesize that spring rains, soil moisture, and relative humidity determine the time of appearance of fruit flies in blackberries in the humid region. Fruit fly abundance should be tracked for several more years to test this hypothesis. In addition, fruit flies were not recovered from fruit samples of the blackberry cultivar Navaho, which is interesting from both an agronomic and scientific perspective.